Trace and Rare Earth Element Partitioning in Organic Fractions of Mudstones during the Oil Formation. (23rd July 2022) - Gao, Ping; Li, Boyuan; Xiao, Xianming
Abstract : In order to investigate trace and rare earth element partitioning in organic fractions of mudstones, this study isolated organic fractions of mudstones, including insoluble organic fraction (kerogen), soluble organic fraction (extract), or expelled hydrocarbon (reservoir solid bitumen), and the isolated organic fractions and their corresponding whole rocks for trace and rare earth element compositions were measured. Analysis of trace and rare earth element compositions in organic fractions of lacustrine and marine mudstones revealed that mudstone kerogens were more enriched in rare earth elements (REE) and redox-sensitive trace elements (e.g., U, Mo, and Ni) relative to corresponding whole rocks. During the oil generation, middle rare earth elements (Sm-Ho), especially Eu, migrated from kerogen to extract more easily than the rest REE. The Eu was easily transferred to soluble hydrocarbon under the acidic and reducing environments formed by oil generation, resulting in the higher concentrations of Eu relative to its neighboring REE (Sm and Gd) and the pronounced positive Eu anomalies. Transition metal elements (e.g., Mo, V, Cr, Co, Ni, Cu, and Zn) also more easily released from kerogen than the rest elements, especially V and Ni. The enrichment and mobilization of trace elements in organic fractions of mudstones, such as Mo, U, V, Ni, and Ba, are closely related with their geochemical behaviors during the depositional and early digenetic processes, providing the potential information for predicting the distribution characteristics of trace elements in the expelled hydrocarbons of mudstones (e.g., crude oil and solid bitumen) and fingerprinting of oil to source.